Direct Synthesis of Hydrogen and Dimethoxylmethane from Methanol on Copper/Silica Catalysts with Optimal Cu+/Cu0 Sites. Issue 5 (6th February 2018) - Wu, Liubi; Li, Bolong; Zhao, Chen
Abstract: Hydrogen is an important sustainable resource, and here we report a catalytic route for the direct production of hydrogen (with a purity of 95 %) and dimethoxylmethane (DMM) from supercritical methanol over a Cu/SiO2 catalyst prepared by deposition–precipitation with ammonia (DPA) at 240°C in a one‐pot process. The procedure starts with methanol dehydrogenation to hydrogen and formaldehyde at the interface of the Cu2 O⋅SiO2 –Cu 0 particle mixture, and subsequently, the formaldehyde intermediate condenses with substantial methanol to form DMM in the liquid phase. The Cu 0, CuO, and chrysocolla species are inactive for hydrogen generation from methanol, and the intrinsic active species for methanol decomposition is the Cu2 O⋅SiO2 –Cu 0 nanoparticle interface, which is produced from the hydrogen reduction of Cu2 Si2 O5 (OH)2 or from the methanol reduction of Cu−O−Si moieties. A correlation between the structure and activity on reduced Cu/SiO2 (DPA) suggested that only Cu 0 was not active, but the combined Cu 0 and Cu + sites with interfaces on SiO2 with an optimal Cu + /Cu 0 ratio of 1.56 were highly active for methanol dehydrogenation and subsequent condensation steps. The developed new catalytic system offers a facile and atom‐economical way to generate pure hydrogen (almost CO free) from liquid methanol that can be used in fuel cell and hydrogen‐involved biomass reactions. Abstract : Cop on to copper : We report a catalytic route for the direct production of hydrogen (with a purity of 95 %) and dimethoxylmethane from supercritical methanol over a Cu/SiO2 catalyst prepared by deposition precipitation with ammonia at 240°C in a one‐pot process.